(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Yoga is a comprehensive spiritual instrument that has many advantages, including bettering health and wellbeing. Asanas (physical postures), pranayama (controlled breathing), and meditation are yoga practices that are frequently used for their health benefits. Yoga may be mistakenly thought of as another form of physical exercise because, when viewed in the context of asanas, it mimics physical exercise more closely. The link between the study of yogic movements and electromyography (EMG) is thoroughly reviewed in this research. Yoga involves a variety of physical postures (asanas) and breathing techniques (pranayama), both of which have been proven to offer several health advantages. Our knowledge of the physiological impacts of yogic movements has greatly benefited from the use of EMG, which monitors muscle activation. It is impossible to draw any conclusions from a survey of the EMG research on several complicated yogic talents, including methodological techniques. We made an effort to establish guidelines for the EMG approach at the outset of this review. An exhaustive examination of the subject of electromyography and yoga is impossible due to the fact that information is dispersed across a wide range of journals, including those devoted to sports sciences, ergonomics, biomechanics, applied physiology, various congress proceedings, and so forth. As a result, numerous crucial elements and perhaps crucial articles may have been missed from our review.